Cholinoceptor Activation Subserving the Effects of Interferon Gamma on the Contractility of Rat Ileum - Enri S. Borda; Leonor Sterin-Borda; Martin Rodriguez; Maria M. E. de Bracco (Mediators of Inflammation)
Recombinant rat interferon γ stimulated the contractility of isolated rat ileum at doses of 4–12 units/ml. Muscarinic cholinoceptors were involved, as treatment of the tissue with atropine prevented the contractile response of the ileum. Furthermore, interferon γ increased the affinity of carbachol for the cholinoceptors and did not change its maximum effect. Neurogenic pathways were also involved since pretreatment of ileum with hexamethonium, hemicholinium or tetrodotoxin impaired the contractile effect of interferon γ. In contrast to the action of exogenous carbachol, the effects of interferon γ are indirect. They appear to involve a G protein regulating phosphoinositide turnover and cytoskeletal structures since they could not be induced in ileum strips that were pretreated with pertussis toxin, phospholipase C inhibitors (2-nitro-carboxyphenyl, NN-diphenyl carbamate and neomycin), cytochalasine B or colchicine.